Synthesis and characterization of non-toxic and thermo-sensitive poly(N-isopropylacrylamide)-grafted cashew gum nanoparticles as a potential epirubicin delivery matrix. (10th December 2016) - Abreu, Clara M.W.S.; Paula, Haroldo C.B.; Seabra, Vitor; Feitosa, Judith P.A.; Sarmento, Bruno; de Paula, Regina C.M.
Highlights: Cashew gum grafted N -isopropylacrylamide was successfully synthesized. The graft copolymer demonstrated thermal responsiveness. The nanoparticles showed no cytotoxic activity against the Caco-2 and HT29-MTX. Copolymer shows good epirubicin association efficiency. Abstract: Cashew gum (CG) was grafted with N -isopropylacrylamide (NIPA) by radical polymerization to originate a stimuli-sensitive copolymer for drug delivery purposes. NMR and IR spectroscopy confirmed the insertion of NIPA onto the cashew gum chains. The graft copolymer (CG:NIPA) demonstrated thermal responsiveness. The critical aggregation concentration of the copolymers at 25 °C was higher than at 50 °C. At temperatures lower than the LCST, the nanoparticle size ranged from 12 to 21 nm, depending on the CG:NIPA ratio, but above the LCST the particles aggregated, increasing the particle size. Regarding the potential for future oral application, the nanoparticles showed no cytotoxic activity against the Caco-2 and HT29-MTX intestine cell lines. Epirubicin was encapsulated into nanoparticles of CG-NIPA (1:1), resulting in a 64% association efficiency and 22% loading capacity. Thus, the CG:NIPA graft copolymer demonstrates good potential for used in controlled drug delivery systems.